Pengaruh Motivasi, Persepsi, Dan Pengetahuan Perpajakan Terhadap Minat Berkarier Sebagai Konsultan Pajak (Studi Pada Mahasiswa S1 Akuntansi Universitas Dharma Andalas) - Syifa Rubia; Nini . (CV. ITTC INDONESIA, 2026)
This study aims to examine and determine the influence of motivation, perception, and tax knowledge on the interest in pursuing a career as a tax consultant, employing a quantitative research method. The population consists of active undergraduate students in the Accounting program at the Faculty of Economics and Business, Dharma Andalas University. A sample of 153 respondents was selected using purposive sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the assistance of SPSS software. The findings indicate that perception and tax knowledge have a positive and significant impact on the interest in becoming a tax consultant. Conversely, motivation does not significantly affect this career interest. This suggests that students' inclination toward a tax consulting career is more influenced by their views on the profession and their level of tax knowledge. The study is expected to contribute to educational institutions in enhancing students' interest in taxation careers by fostering positive perceptions and improving tax knowledge.